Standardised tests in mice and cattle for the detection of drug resistance in tsetse-transmitted trypanosomes of African domestic cattle - Eisler, M.C; Brandt, J; Bauer, B; Clausen, P.-H; Delespaux, V; Holmes, P.H; Ilemobade, A; Machila, N; Mbwambo, H; McDermott, J; Mehlitz, D; Murilla, G; et al. (Veterinary parasitology, 2001)
Resistance to the drugs used to control African animal trypanosomosis is increasingly recognised as a constraint to livestock production in sub-Saharan Africa. The most commonly used tests for detection of trypanocidal drug resistance are tests using mice or ruminants, but these suffer from lack of standardisation and hence it may be difficult to compare the results of different investigators. Tests in mice are less expensive than tests in ruminants, but while tests in mice they may be useful as a general guide to resistance in a geographic area they should not be extrapolated to cattle on an individual trypanosome level. Moreover, the commonly used protocols are too laborious for their application to large number of trypanosome isolates on an area-wide basis. This paper presents guidelines for standardised testing of trypanocidal drugs in vivo, and introduces a simplified single-dose test for use in mice, which is convenient for use in areas with limited laboratory facilities. The single-dose test is appropriate for characterisation of geographic areas in terms of trypanocidal drug resistance using large numbers of trypanosome isolates, for making comparisons between areas, and for monitoring changes in trypanocidal drug resistance over time. Multiple-dose tests may be used to determine the degree of resistance of individual stabilates to be determined precisely in mice are also described, but for logistical reasons these will rarely be conducted on more than a few stabilates, and testing of a larger number of stabilates in the single-dose test will generally provide more useful information. Finally, we describe tests in cattle that may be used to determine the efficacy of recommended curative doses of trypanocidal drugs for the treatment of infection with individual trypanosome isolates, including Trypanosoma vivax, which is rarely infective for mice.